2019
DOI: 10.1155/2019/8765970
|View full text |Cite
|
Sign up to set email alerts
|

On Stability of Multi‐Valued Nonlinear Feedback Shift Registers

Abstract: Nonlinear feedback shift registers (NFSRs) are the main building blocks in many convolutional decoders, and a stable NFSR can limit decoding error propagation. Due to lack of efficient algebraic tools, the stability of multi-valued NFSRs has been much less studied. This paper studies the stability of multi-valued NFSRs using a logic network approach. A multi-valued NFSR can be viewed as a logic network. Based on its logic network representation, some sufficient and necessary conditions are provided for globall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Their method for constructing reliable FSRs indicated that the number of reliable FSRs is 2 2 n −4 Φ(n) (n > 5) times of that constructed by the previous method. The methods given in [91,92] can be applied to multi-valued NFSRs, and can construct stable NFSRs. Furthermore, the literature [93,95] addressed the stability issues of (n, k) NFSR and Grain-like cascade NFSRs, respectively.…”
Section: Definition 8 ([85]mentioning
confidence: 99%
See 2 more Smart Citations
“…Their method for constructing reliable FSRs indicated that the number of reliable FSRs is 2 2 n −4 Φ(n) (n > 5) times of that constructed by the previous method. The methods given in [91,92] can be applied to multi-valued NFSRs, and can construct stable NFSRs. Furthermore, the literature [93,95] addressed the stability issues of (n, k) NFSR and Grain-like cascade NFSRs, respectively.…”
Section: Definition 8 ([85]mentioning
confidence: 99%
“…These results are helpful to the theoretical analysis of NFSRs, and have reference significance for the design of decoding algorithm. NFSRs, iteration method shown in Theorem 1 stability 2016 [85] NFSRs, reduce the computational complexity driven stability 2017 [93] (n, k) NFSRs stability 2018 [78] NFSRs with periodic input stability 2019 [91,92] multi-valued NFSRs, construct stable NFSRs stability 2020 [95] Grain-like cascade NFSRs stability 2021 [87] monotonous FSRs, construct reliable FSRs stability…”
Section: Definition 8 ([85]mentioning
confidence: 99%
See 1 more Smart Citation